UV reflectance as a cue in egg discrimination in two Prinia species exploited differently by brood parasites in Taiwan. (4th April 2013) - Yang, Canchao; Wang, Longwu; Hsu, Yu‐Cheng; Antonov, Anton; Moksnes, Arne; Røskaft, Eivin; Liang, Wei; Stokke, Bård G.; Ishtiaq, Farah
<x xml:space="preserve">Abstract</x> Birds are capable of seeing the ultraviolet light (UV) spectrum and as a consequence have evolved UV‐reflective structures with signalling functions. Avian eggs also reflect in the UV spectrum but the importance of UV egg matching in egg rejection decisions has been equivocal. Here we conducted egg rejection experiments in the congeneric and sympatrically breeding Yellow‐bellied Prinia Prinia flaviventris and Plain Prinia Prinia inornata in Taiwan to assess the role of UV as a cue in egg discrimination. Yellow‐bellied Prinia is a host of Oriental Cuckoo Cuculus optatus, whereas Plain Prinia is not. We coated one prinia egg in the experimental clutches with a cream containing a UV‐blocking agent, while the rest of the eggs were coated with cream only. We also experimentally parasitized prinias with non‐mimetic model eggs with reduced UV reflectance. Yellow‐bellied Prinia and Plain Prinia rejected their own UV‐blocked eggs in 18.2 and 8.3% of the experiments, respectively, and the difference was not significant. However, Yellow‐bellied Prinia rejected 100% of the non‐mimetic eggs, whereas the Plain Prinia rejected only 5%. Hence, UV reflectance alone is a cue in egg discrimination, but the importance of reflectance outside the UV spectrum in these two prinia species is much more responsive to selection as a consequence of brood parasitism.